Advanced phytochemical screening of solanum torvum (fruits, leaves and stems) / Nurfarahin Mahmud - Mahmud, Nurfarahin (Faculty of Applied Sciences, 2017)
Three parts of S. torvum plant were obtained which are fruits, leaves and stems. Extraction process of S.torvum takes placed by using ethanol solvent and cold extraction method. The preliminary phytochemical analysis of the crude extracts of the S. torvum plant indicated the presence of major phytochemical compounds, including alkaloid, flavonoid, glycoside, phenol, saponin, steroid, tannin and terpenoid which responsible for the observed antioxidant activity, antimicrobial activity, anti inflammatory activity and anticancer activity. The observed results support some traditional medicinal plants as promising sources of potential antioxidants and medicinal compounds. Gas Chromatography-Mass Spectrometry (GC-MS) of the ethanolic extract of the S. torvum is presented in Mass spectra by using helium as carrier gas. The fragmentation patterns of the mass spectra were compared with those of the known compounds stored in the National Institute of Standards and Technology (NIST) research library. In the GCMS analysis, about seven active components were detected which are hexadecanoic acid or ethyl ester, butanoic acid, urea, N-methyl-N-nitroso, 1- tetradecanamine or N,N-dimethyl, glycidyl palmitate, n- hexadecanoic acid and octadecanoic acid. The identification of photochemical compounds is based on peak area, molecular weight and formula.